History Matters : Contemporary Poetry on the Margins of American Culture. - Sadoff, Ira (UPCC book collections on Project MUSE., 2009)
In this capacious and energetic volume, Ira Sadoff argues that poets live and write within history, our artistic values always reflecting attitudes about both literary history and culture at large. History Matters does not return to the culture war that reduced complex arguments about human nature, creativity, identity, and interplay between individual and collective identity to slogans. Rather, Sadoff peels back layers of clutter to reveal the important questions at the heart of any complex and fruitful discussion about the connections between culture and literature.